DYNAMIC CHARACTERISTICS OF THE FREQUENCY-LOCKED LOOP AT THE MOMENT OF TRACKING LOSS OF THE FREQUENCY OF POINT TARGET - V. A. Kovrigin (Научный вестник МГТУ ГА, 2016)
Performance features of the frequency-locked loop in the close range zone used as a narrow-band filter, keeping track of the Doppler frequency, are analyzed. The results of the calculations of dynamic characteristics of the FLL system in the moment of tracking loss in the range of meeting conditions are given.